A Legal Controversy Surrounding the Clean Power Plant: A History, Overview, and Analysis - Duffy, Ryan (Colloquium: The Political Science Journal of Boston College, 2025)
In 2014, the Obama Administration unveiled the Clean Power Plan (CPP), an Environmental Protection Agency (EPA) set of regulations aimed at reducing greenhouse gas emissions by targeting power plants. Since its introduction, the plan has faced backlash from Republicans, members of Congress, states, and industry. Multiple parties have challenged the plan’s legal basis on the grounds that it is unconstitutional and beyond the scope of the EPA. This paper aims to explore the legal debate surrounding the CPP, which is currently being fought in the U.S. Supreme Court and likely to be scrapped by the incoming Trump administration. The paper starts with a brief legislative and regulatory primer and then explores the verdicts of two related Supreme Court cases. Since the CPP is a directive aimed at reining in greenhouse gas emissions, the paper gives constitutional, political, and legal consideration to the issue of climate change.